Optimizing Lifeboat Maintenance to Ensure They Are Suitable for Use in the Event of an Accident - Diaz Arifiansyah; Muhamad Imam Firdaus; Bugi Nugraha; Dety Sutralinda (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Maritime transport supports 80% of global trade, but inconsistent lifeboat maintenance threatens emergency safety, especially on Indonesian short voyage vessels such as the MV Tanto Bersinar. This study identifies factors inhibiting lifeboat maintenance optimization and proposes procedures in accordance with SOLAS. Using a qualitative descriptive method, purposive sampling targeted key crew (Third Officer, Third Engineer) for 12 months through interviews, observations, literature studies, and documentation. Data analysis followed reduction, presentation, and conclusion. The results found davit corrosion, wire rope friction, no engine test-run, incomplete PMS documentation, and limited short voyage time as gaps to SOLAS III/20 and MSC.402(96). Optimization requires scheduled operational tests, certified training, and spare parts stock. The conclusion recommends strengthening the PMS and authorized servicing for lifeboat readiness, minimizing evacuation risks